Los "progymnasmata" en los "Praeceptiorum Rhetoricarum Libri V et Exercitationum Libri II" de Georg Henisch: fuentes y materiales - Rodríguez Herrera, Gregorio (Euphrosyne: Revista de filología clássica, 2016)
Georg Henisch included in the second book of his Exercitationum libri fourteen progymnasmata. In this article we study the sources and materials of these progymnasmata and show their particular dependence, on the one hand, on Aphtonius' translation of Agricola-Cataneus, and, on the other hand, on Burchard Harbart's commentaries on Aphtonius.